Analisis Pengaruh Media Pendingin Terhadap Kekerasan Baja S45C Pada Proses Hardening-Tempering - Arlingga, Alfian Siswara; -, Somawardi; -, Sugianto (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2021)
This study used an experimental method, in the form of the heat treatment hardening 930⁰C with the variations in the cooling media of the coconut water, table salt water, mineral waterwater, coolant radiator, and dromus water and variations in temperatures of tempering 200⁰C, 420⁰C, and 600⁰C, the specimens were cylindrical in diameter 25 mm and 20 mm in length, this study aims to determine the optimum hardness value of S45C steel specimens due to the heat treatment process hardening-tempering. From the results of the study, there is the effect of hardening 930⁰C there is the most optimal hardness value found in coconut water cooling media with the hardness level of 53.5 HRC. Under the influence of tempering 200⁰C there is the optimum hardness value found from the influence of mineral water cooling media with the hardness level of 50.7 HRC, while the influence of tempering 420⁰C there is the most optimal hardness value from the influence of mineral water cooling media with the hardness level of 41.8 HRC, and for tempering effect 600⁰C there is the most optimal hardness value available from the influence of the coconut water cooling media with the hardness level of 35.93 HRC.